The Crystal Chemistry of Francolite in Akashat Phosphorites (Middle Paleocene), Iraqi Western Desert - Al-Youzbakey, Kotayba Tawfiq; Al-Dabbagh, Salim Mahmood (Journal of natural sciences, life and applied sciences, 2020)
The geochemical study of concentrated phosphatic grains show two main groups of elements, the first one represents (CaO, P2O5, F, CO3, SO3, Na, Sr and Cl) which are considered in determining the chemical formula of francolite, and are positively correlated with some trace elements (e.g. U, Y, REE, Cr, Mn and V). The second group of elements represents the clay minerals (palygorskite, sepiolite and montmorillonite). These minerals found in phosphatic grains in fractures and between coated layers by organic activity. This study suggests that the couple substitution of anions and cations for calcium, phosphorous and fluorine in francolite don’t take place as coupled substitution but as open substitution of many anions and cations depending on the conformity in the coordination numbers of any site. In the same time, it is a compound substitution because of sharing many ions in the process. The decreasing in moles/formula of Na, S and Cl in the chemical formula of francolite indicates the slightly increasing in salinity and alkalinity of seawater. Sr reflects the effect of chemical composition of interstitial water on the francolite formation. CO3 mole/formula shows the role of the diagenesis process on the growth of francolite. The low Mg mole/formula reflects the consumption of magnesium in dolomite and clay minerals which enable the growth of phosphatic grains.